Analisis Pemanfaatan Fintech Qris Terhadap Efisiensi Transaksi dan Kepuasan Umkm di Indonesia - Keisha Trideswita Maharani; Raisa Martiza (LPPM Politeknik Pratama, 2026)
The The implementation of the Quick Response Code Indonesian Standard (QRIS) by Bank Indonesia serves as a strategic innovation to unify various digital payment systems into a single national standard. This study aims to analyze the impact of QRIS implementation on transaction efficiency and the satisfaction of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Utilizing a qualitative descriptive method, this research collects data through a literature study of official Bank Indonesia reports, publications from the Indonesian Fintech Association (AFTECH), and scientific journals from 2021–2024. The findings indicate that QRIS usage significantly enhances transaction efficiency by reducing queue times, minimizing recording errors, and eliminating the cost of EDC machines. Furthermore, QRIS positively contributes to MSME satisfaction by expanding market reach and building business credibility. However, adoption faces challenges such as low digital literacy, uneven internet infrastructure, and the burden of Merchant Discount Rate (MDR) fees for micro-enterprises. The study recommends tiered MDR fee incentives and intensified digital education programs